Perception of Sunflecks by the UV-B Photoreceptor UV RESISTANCE LOCUS8. Issue 1 (12th March 2018) - Moriconi, Victoria; Binkert, Melanie; Costigliolo, Cecilia; Sellaro, Romina; Ulm, Roman; Casal, Jorge J.
Abstract : Sunflecks that penetrate through canopy gaps transiently interrupt shade and modify the activity of the UV-B photoreceptor UVR8 to mediate growth and gene expression responses. Abstract: Sunflecks, transient patches of light that penetrate through gaps in the canopy and transiently interrupt shade, are eco-physiologically and agriculturally important sources of energy for carbon gain, but our molecular understanding of how plant organs perceive and respond to sunflecks through photoreceptors remains limited. The UV-B photoreceptor UV RESISTANCE LOCUS8 (UVR8) is a recent addition to the list of plant photosensory receptors, and we have made considerable advances in our understanding of the physiology and molecular mechanisms of action of UVR8 and its signaling pathway. However, the function of UVR8 in the natural environment is poorly understood. Here, we show that the UVR8 dimer/monomer ratio responds quantitatively and reversibly to the intensity of sunflecks that interrupt shade in the field. Sunflecks reduced hypocotyl growth and increased CHALCONE SYNTHASE ( CHS ) and ELONGATED HYPOCOTYL5 gene expression and CHS protein abundance in wild-type Arabidopsis ( Arabidopsis thaliana ) seedlings, but the uvr8 mutant was impaired in these responses. UVR8 was also required for normal nuclear dynamics of CONSTITUTIVELY PHOTOMORPHOGENIC1. We propose that UVR8 plays an important role in the plant perception of and response to sunflecks.